Impact of a Comfortable in our Skin interactive workshop on social media awareness and self‐confidence in adolescents. Issue 4 (3rd May 2022) - Mumber, Hannah E.; Rashid, Sarem; Carey, Grace; Navarro, Alexis; Oh, Eric; Nasir, Muhammad; Lee, Margaret S.
Abstract: Social media use contributes to body dissatisfaction and reduced quality of life among adolescents. This study examines the impact of social media use and skin conditions on body image and suggests that a Comfortable in Our Skin (CIOS) pilot community‐based workshop may promote healthier body image and social media usage among urban adolescents.